Regular Health Education Sessions on Routine Immunization in Public and Private Schools. - Aftab Ahmed, Hanna Khair Tunio, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Problem Statement: Engagement of the Education department along with health department in arranging Health education session focusing parents regarding routine immunization of their children to save 400,000 lives of Pakistani children annually from the preventable diseases